Population Fluctuation and Altitudinal Distribution of Tetraleurodes perseae (Nakahara) (Hemiptera: Aleyrodidae) in Avocado (Lauraceae) in Morelos, Mexico. Issue 1 (22nd September 2016) - García-Palacios, Daniel; Bautista-Martínez, Néstor; Lagunes-Tejeda, Ángel; Carrillo-Sánchez, José Luis; Nieto-Ángel, Daniel; García-Gutiérrez, Cipriano
Abstract: Although whiteflies Tetraleurodes perseae (Nakahara) (Hemiptera: Aleyrodidae) are considered a secondary pest of avocado crops, their presence and the damages that they cause can decrease crop vigor and affect production. The objective of the present work was to determine the population fluctuation and altitudinal distribution of the T. perseae Nakahara whitefly in avocado trees, as well as to determine the number of possible generations in one year. The study was done in three orchards in Morelos state, located at different altitudes, from February 2014 to April 2015. Samplings were done every 21 days from 10 randomly chosen trees in each orchard. The samples were taken randomly from the middle stratus (1.6 m in height) of each tree; in buds or young leaves for the number of adults and leaves only for nymphs. Additionally, two yellow traps (7 × 14 cm) with glue were placed in each tree for adult samplings. Data were collected regarding vegetative budding, rainfall, relative humidity, and temperature. T. perseae was present in all three sampled orchards, with a greater presence in the lowest orchard, during the whole study period. In the orchard with the lowest altitudinal gradient (1, 736 masl), 11 whitefly generations developed; 10 generations developed in the medium gradient orchard (1, 934 masl); and 8 generations developed in the highest orchard (2, 230 masl). The adults showed a positive relationship with regard to vegetative buds, while the nymphs had a negative relationship with regard to relative humidity. The rest of the parameters showed diverse effects on the species depending on the altitude of the orchard.